Effect of polyurethane matrix and steel fiber in combination with glass fiber or basalt fiber on the properties of hybrid composite laminates - Fayzulla, Bayan Jabbar; Eroglu, Mehmet; Erklig, Ahmet (Walter de Gruyter Gmbh, 2023)
Polyurethane is a versatile polymer with a high degree of toughness and ductility used in a wide variety of applications. In this study, two-part thermoset polyurethane was used as a matrix material to prepare hybrid and non-hybrid composites. Hybrid laminates were prepared by combining either glass fiber or basalt fibers with steel fibers. The mechanical properties of prepared composite specimens were characterized and scanning electron microscope (SEM) observation was performed around the fracture region of the tested specimens. The results revealed a significant increment in tensile strength, and flexural strength in BS1-PU (8 layers of basalt-1 layer of steel) hybrid laminate by 357.74 % and 64.59 %, respectively, compared to steel fibers reinforced polyurethane composites. Furthermore, GS4-PU hybrid composite (5 layers of glass-4 layers of steel) achieved an improvement in tensile strain by 12.07 %, flexural strain by 25.32 %, and absorbed energy by 18.21 %, compared to glass fibers reinforced polyurethane composite. Moreover, the SEM observations revealed that the replacement of some basalt and glass layers with steel layers leads to a positive hybridization effect of the overall produced hybrid composites.
Keywords: absorbed energy; hybridization; mechanical properties; polyurethane; steel fibers